Intradialytic Complications and its Associated Factors Among Chronic Kidney Disease Patients in a Tertiary hospital - Sah, Dilip; KC, Heera; Shah, Sweta; Rai, Rabin (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Chronic kidney disease is a public health problem affecting millions of people worldwide. Hemodialysis is a life-saving renal replacement therapy for patients with chronic kidney disease(CKD), but it is not without risks. Intradialytic complications, which occur during hemodialysis sessions, can have a significant impact on patients' well-being, treatment outcomes, and overall quality of life. This article aims to identify the intradialytic complications and its associated factors in patients with chronic kidney disease undergoing hemodialysis in a tertiary hospital of eastern Nepal. Methods An observational cross-sectional study design was employed among 72 patients receiving hemodialysis treatment at Birat Medical College Teaching Hospital from 28 January to 20 May 2023. Total enumeration sampling technique with a structured questionnaire via interview and observation technique was used for data collection. Collected data was entered in Microsoft Excel sheet and transferred to SPSS version 17. Frequency, mean, range, and standard deviation was calculated. Chi square test was used to determine the association. P-value <0.05 was considered statistically significant. Results All patients undergoing hemodialysis experienced at least one intradialytic complication. The most common complications reported were nausea/vomiting 59(81.9%) and chills/rigor 57(79.2%). Hypoglycemia was observed in 23.6% of patients, hyperglycemia in 12.5%, hypotension in 8.3%, and arrhythmia in 2 patients. Conclusions Intradialytic complications are common among chronic kidney disease patients undergoing hemodialysis.The associations between age, dialysis frequency, preexisting diabetes, hypertension, and specific complications emphasize the need for individualized care and tailored interventions.